Fingertip advanced glycation end products and psychotic symptoms among adolescents - Mitsuhiro Miyashita (Nature Portfolio, 2021)
Abstract Case control studies have suggested that advanced glycation end products play a key role in the pathophysiology of chronic schizophrenia. However, the longitudinal association between advanced glycation end products and psychotic symptoms among drug-naïve adolescents remains unclear. This study examined whether advanced glycation end products could predict the trajectory of psychotic symptoms in drug-naive adolescents using data from prospective population-based biomarker subsample study of the Tokyo Teen Cohort. A total of 277 community-dwelling adolescents aged 13 years without antipsychotic medication were analyzed. Fingertip advanced glycation end products were measured in adolescents using noninvasive technology that can be used quickly. The trajectory of psychotic symptoms in a 12-month follow-up was assessed by experienced psychiatrists using a semi-structured interview. Of the 277 participants, 13 (4.7%) experienced persistent psychotic symptoms (psychotic symptoms at baseline and follow-up), 65 (23.5%) experienced transient psychotic symptoms (psychotic symptoms at baseline or follow-up), and 199 (71.8%) did not have psychotic symptoms. Multinomial logistic regression analysis adjusted for age and sex revealed that baseline fingertip advanced glycation end products might predict the risk of persistent psychotic symptoms (odds ratio = 1.68; 95% confidence interval, 1.05–2.69; P = 0.03). Altogether, fingertip advanced glycation end products potentially predicted the trajectory of psychotic symptoms among drug-naive adolescents, which indicated its involvement in the pathophysiology of early psychosis. Further studies are required to identify strategies to reduce adolescent advanced glycation end products, which may contribute to preventing the onset of psychosis.